Leverage, ESG, and Earnings Management: Their Interaction on Tax Avoidance in Indonesia’s Coal Sector - Ramadani, Sufi Nadya Firlian; Akbar, Taufik (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research project examines how earnings management and ESG scores affect tax avoidance tactics used by coal mining firms listed on the Indonesia Stock Exchange between 2020 and 2023. This research utilizes a quantitative methodology, specifically panel data regression and Moderated Regression Analysis (MRA), to examine the moderating effect of leverage on these relationships. Secondary data were sourced from corporate financial statements, sustainability reports, and other ESG databases. The results demonstrate a strong positive link between ESG scores and tax avoidance. Accordingly, businesses with higher ESG scores are more likely to engage in tax avoidance, perhaps using their favorable environmental reputation as an excuse for aggressive tax planning. On the other hand, tax avoidance in the industry is not much impacted by earnings management. Moreover, leverage was determined not to influence the association between ESG scores or earnings management and tax avoidance. These data imply that tax avoidance in coal mining is driven more by corporate strategies balancing reputation and financial performance than by earnings manipulation or debt structure. The study contributes to understanding corporate tax behavior in resource-intensive industries and provides insights on the complexities of ESG and tax compliance for policymakers and stakeholders.